2008
DOI: 10.1007/s00432-008-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II trial of TAC-101, an oral synthetic retinoid, in patients with advanced hepatocellular carcinoma

Abstract: 20 mg of TAC- was well tolerated. Significant disease stabilization (12/21 pts, 57%), 2 late PRs, and prolonged MS (19.2 months) suggest that TAC-101 provides meaningful patient benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…(7,8) Higginbotham et al reported the results of pharmacokinetic studies of TAC-101 in patients with advanced hepatocellular carcinoma treated in the United States. (8) The mean pharmacokinetic parameters (t max , 4.3 h; C max , 242 ng/mL; AUC 0-24 , 3067.6 ng h/mL; AUC inf , 4241.1 ng h/mL) obtained for a dose of 20 mg were generally consistent with our data in Japanese patients. The slightly lower C max and AUCs values in the American study might be attributed to general differences in body size between Caucasians and Japanese.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(7,8) Higginbotham et al reported the results of pharmacokinetic studies of TAC-101 in patients with advanced hepatocellular carcinoma treated in the United States. (8) The mean pharmacokinetic parameters (t max , 4.3 h; C max , 242 ng/mL; AUC 0-24 , 3067.6 ng h/mL; AUC inf , 4241.1 ng h/mL) obtained for a dose of 20 mg were generally consistent with our data in Japanese patients. The slightly lower C max and AUCs values in the American study might be attributed to general differences in body size between Caucasians and Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…The results for efficacy in this study were also similar to those in the study performed in the United States. (8) Unfortunately, tumor shrinkage was not evident, and the median TTP seemed to be unfavorable on the basis of MST. However, we believe that further evaluations are warranted, because the mechanisms of action of TAC-101 and other retinoids are considered cytostatic as opposed to cytotoxic, and the TTP in this study may be comparable to those in studies of sorafenib (2.8-5.5 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible target in endocrine therapy is the retinoid X receptor (RXRα), which is malfunctioning in HCC due to phosphorylation by the Ras-MAPK signaling pathway [16]. A recent phase I/II study of an oral synthetic retinoid (TAC-101) has reported good tolerability and a significant disease stabilization effect in 12 out of 21 patients [17]. However, because of the limited number of reports, further investigation is needed to warrant endocrine therapy for HCC.…”
Section: Systemic Therapy For Hccmentioning
confidence: 99%
“…PTK787 (Vatalanib) [143] , AZD2171 (Cediranib) [144] , SU6668 (TSU-68) [145] ) under investigation in advanced HCC; however, they are beyond the scope of this article and are reviewed elsewhere [101,110,146,147] . Other novel strategies apart from monoclonal antibodies and tyrosine kinase inhibitors include the retinoid compound TAC101 [148] , the cell cycle inhibitor flavopiridol [149] , the proteasome inhibitor bortezomib [150] , and histone deacetylase inhibitors for targeting epigenetic alterations. Some of them are already in phase I-II clinical trials.…”
Section: Additional Agents Under Investigationmentioning
confidence: 99%